2015
DOI: 10.1515/geoca-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Syntectonic Hydrothermal Veins in the Igneous Rock of Teschenite Association (Outer Western Carpathians, Czech Republic): Growth Mechanism and Origin of Fluids

Abstract: Hydrothermal mineralization hosted by the Lower Cretaceous igneous rock of the teschenite association at Jasenice (Silesian Unit, Flysch Belt, Outer Western Carpathians) occurs in two morphological types -irregular vein filled by granular calcite and regular composite vein formed by both fibrous and granular calcite and minor chlorite, quartz, and pyrite. Crosscutting evidence indicates that the granular veins are younger than the composite vein. The composite vein was formed by two mechanisms at different tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Such a trend is very characteristic for low-temperature post-magmatic hydrothermal mineralizations hosted by teschenites in the Silesian Unit (e.g., Dolníček et al 2010 a,b;Urubek et al 2014). …”
Section: Fluid Inclusionsmentioning
confidence: 93%
See 4 more Smart Citations
“…Such a trend is very characteristic for low-temperature post-magmatic hydrothermal mineralizations hosted by teschenites in the Silesian Unit (e.g., Dolníček et al 2010 a,b;Urubek et al 2014). …”
Section: Fluid Inclusionsmentioning
confidence: 93%
“…In addition, cementation of fissures and vesicles by hydrothermal minerals gave rise to abundant hydrothermal veins and amygdules. Recent studies (Dolníček et al 2010 a,b;Dolníček et al 2012;Urubek et al 2014;Kropáč et al 2015) revealed that multiple stages of hydrothermal activity occurred in this rock environment. The most important event was early post-magmatic alteration, which took place immediately after solidification of the host rock, when fluid circulation was allowed due to heat flow associated with the host intrusion (e.g., Dolníček et al 2010 a,b).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations